The Implementation of Pop-Up Book Media: Potential Implication on Mathematics and Science Learning Outcomes - Akina Akina; Dian Nitami Rukmana Paeri; Mufidah Mufidah; Nuraini Nuraini (Jurnal Penelitian Pendidikan IPA, 2023)
Mathematics is important to the broader implications for science education, as science and mathematics are inherently interconnected. The use of interactive and engaging media such as pop-up books can be a valuable tool for teaching natural science concepts and improving student learning outcomes. This study aims to improve students' mathematics learning outcomes through the implementation of pop-up media during the learning process. The current study also describes potential implication of the result to the natural science learning. This research is classroom action research (CAR). This research was conducted at SD Inpres Baru with 16 third grade students as subjects for two cycles. Research data were analyzed descriptively-quantitatively. Data on student learning outcomes were collected using multiple-choice tests. In addition, observation sheets are also used to collect data on teacher and student activities. The results of the research in cycle I showed that the average student score reached 68.87 with classical completeness reaching 43.75%, while the results of observations of teacher activity (68%) and students (69%) were in the sufficient category. In cycle II, the average student score increased to 87 with classical completeness reaching 87.5%. There were better teacher (89%, good category) and student (91%, very good category) activity compared to the results in cycle I. Based on the results of the study, it can be concluded that the implementation of Pop-up Book learning media in learning mathematics can improve students' learning outcomes on flat shape material. The result can be applied to natural science teaching as well, where teachers need to be more active and effective in guiding students in experiments and demonstrations, and ensure that students are actively participating in the learning process.